Development of face processing: are there critical or sensitive periods?. (December 2020) - Pascalis, Olivier; Fort, Mathilde; Quinn, Paul C
Highlights: Literature suggests the existence of a sensitive period for face processing until 10–12 years of age. However, there is no clear evidence of a critical period for face processing. Some evidence suggests that face and language sensitive periods interact. Studies need to determine if specific face processes have distinct sensitive periods. Future research should investigate links in sensitive periods for faces and language. Abstract : The existence of critical or sensitive periods has been argued for cognitive functions such as language, which allows for communication with conspecifics. Faces also play a crucial role in establishing social communication. Here we discuss if critical or sensitive period concepts apply to face processing. We describe how experience shapes face processing during development. While there is not clear support for a critical period, there is some evidence of a sensitive period, with the face processing system showing early sensitivity to experience in the first year, remaining flexible until 10–12 years, and becoming less sensitive to experience thereafter. We also discuss possible links between sensitive periods for faces and language. We conclude that sensitive periods may reflect the need to adapt rapidly to the communication culture within one's native social group, while retaining a degree of openness to perturbations to one's local environment that can occur across the lifespan.